R&D Subsidies and Technological Progress in the Chinese ICT Manufacturing Industry - Junjun Li (International Telecommunications Society (ITS), 2022)
In the past decades, the Chinese ICT industry has received fiscal, taxation, and financial policy support in technology R&D. This research adopts causal inference methods for mediation analysis with interaction to empirically examine the direct and indirect effects of R&D subsidies in the Chinese ICT manufacturing industry. We found that the impact of R&D subsidies on private R&D expenditure and innovation outputs is positive and statistically significant. However, higher subsidy intensity crowds out private R&D expenditures. Second, in the Eastern region, firms invest more in R&D but more in incremental rather than radical innovation. And, the enterprise average private R&D expenditure is insufficient in the ECE sector. Finally, openness and information levels positively contribute to innovation outputs. Based on the findings, we propose several policy suggestions.
Keywords: 330; R&D subsidies; innovation output; private R&D investment; Chinese ICT manufacturing; causal mediation analysis